Effect of advanced glycation endproducts on the secretion of insulin-like growth factor-I and its binding proteins: role in osteoblast development - McCarthy, Antonio Desmond (2001)
In chronically uncompensated diabetes mellitus, an increase has been observed in the content of advanced glycation endproduct (AGE)-modified proteins in various tissues, including bone. This increase can lead to a local imbalance in the secretion of cytokines and growth factors, and has been implicated in the pathophysiology of the longterm complications of diabetes. We have previously shown that the proliferation and differentiation of UMR106 rat osteosarcoma and MC3T3E1 mouse calvaria-derived cell lines are regulated by AGE-modified proteins, possibly through the recognition of these AGEs by specific membrane-associated receptors. In the present study, we investigated the effects of AGE-proteins on the secretion of insulin-like growth factor-I (IGF-I) and its binding proteins (IGFBPs) by both osteoblast-like cell lines. In the case of MC3T3E1 cells, this was studied throughout their successive stages of development: proliferation, differentiation and mineralisation. For every condition, cells were incubated 24 hours with increasing concentrations of either bovine serum albumin (BSA) or AGE-BSA. IGF-I in conditioned media was separated from IGFBPs by acid gel filtration-centrifugation, and measured by radioimmunoassay. IGFBPs in conditioned media were analysed by a semi-quantitative western ligand blot. In UMR106 cells, low doses of AGE-BSA significantly decreased the secretion of both IGF-I (56% of control) and a 24 kDa IGFBP (80% of control). Results for MC3T3E1 cells, which predominantly secrete 29 kDa IGFBPs, were dependent on the stage of development. In proliferating preosteoblastic cells, AGE-BSA decreased the secretion of IGF-I (34%-37% of control) while increasing the secretion of IGFBP (124%-127% of control). On the other hand, secretion of these components of the IGF system by mature (differentiated) cells was unaffected by the presence of AGE-BSA. When these cells finally attained mineralisation, incubation with AGE-modified BSA provoked an increase both in IGFBP (131%-169% of control) and in IGF-I secretion (119%-123% of control). The presented evidence suggests that the modulation of growth and development by AGE-modified proteins, previously described for both cell lines, could be the result of an autocrine-paracrine mechanism involving the IGF-IGFBP system.